BAHTSUL MASAIL MULTIDISIPLINER: Pembaruan Metodologis Ijtihad Kolektif NU - Muhammad Adib (MAQASHID Jurnal Hukum Islam, 2022)
this paper offers the idea of a multidisciplinary Bahtsul Masail, as a methodological renewal of NU's collective ijtihad forum. This idea is based on three aspects of scientific modality in Bahstul Masail, namely the very nature of tradition, the manhaji mode of thinking in the use of the qauli method, and the problem analysis framework as a result of the 1992 NU National Conference in Lampung . Based on these three aspects, the reform of Bahtsul Masail was carried out by repositioning the problem analysis framework as the grand design of the entire methodological framework in Bahtsul Masail.